Risk : an introduction : the concepts of risk, danger and chance - Ale, Ben J. M. (Routledge, 2009)
"Investments, global warming and crossing the road - risk is a factor embedded in our everyday lives but do we really understand what it means, how it is quantified and how decisions are made? In six chapters Ben Ale explains the concepts, methods and procedures for risk analysis and in doing so provides an introductory understanding of risk perception, assessment and management." -- Publisher's description